How law can help solve the collective action problem of antimicrobial resistance. (3rd July 2019) - Hoffman, Steven J.; Bakshi, Reema; Rogers Van Katwyk, Susan
Abstract: Antimicrobial resistance is a global collective action problem with dire consequences for human health. This article considers how domestic and international legal mechanisms can be used to address antimicrobial resistance and overcome the governance and political economy challenges that accelerate it.